The Effect of Leverage, Firm Size, Profitability, and Liquidity on Hedging Decisions - Heri Purwanto; Putra, Rosyid Nur Anggara (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
Purpose: This study aims to determine the effect of leverage, firm size, profitability, and liquidity on hedging decisions of manufacturing companies listed on the Indonesia Stock Exchange (IDX) Methodology: The sample in this study are 22 manufacturing companies listed on the IDX from 2014 to 2019. This research uses the logistic regression analysis technique. Findings: The results show that the variable leverage, firm size, and profitability have a positive effect and are significant on hedging decisions, while the liquidity variable has no effect on hedging decisions. Novelty: This study continues previous research by using a different population, adding independent variables, and using the manufacturing sector. Keywords: Leverage, Firm Size, Profitability, Liquidity, Hedging